Unstable Prefrontal Response to Emotional Conflict and Activation of Lower Limbic Structures and Brainstem in Remitted Panic Disorder - Chechko, Natalya; Wehrle, Renate; Erhardt, Angelika; Holsboer, Florian; Czisch, Michael; Sämann, Philipp G. (PloS one, 2009)
The neural mechanisms of panic disorder (PD) are only incompletely understood. Higher sensitivity of patients to unspecific fear cues and similarities to conditioned fear suggest involvement of lower limbic and brainstem structures. We investigated if emotion perception is altered in remitted PD as a trait feature. We used blood oxygenation level-dependent (BOLD) functional magnetic resonance imaging (fMRI) to study neural and behavioural responses of 18 remitted PD patients and 18 healthy subjects to the emotional conflict paradigm that is based on the presentation of emotionally congruent and incongruent face/word pairs. We observed that patients showed stronger behavioural interference and lower adaptation to interference conflict. Overall performance in patients was slower but not less accurate. In the context of preceding congruence, stronger dorsal anterior cingulate cortex (dACC) activation during conflict detection was found in patients. In the context of preceding incongruence, controls expanded dACC activity and succeeded in reducing behavioural interference. In contrast, patients demonstrated a dropout of dACC and dorsomedial prefrontal cortex (dmPFC) recruitment but activation of the lower limbic areas (including right amygdala) and brainstem. This study provides evidence that stimulus order in the presentation of emotional stimuli has a markedly larger influence on the brain's response in remitted PD than in controls, leading to abnormal responses of the dACC/dmPFC and lower limbic structures (including the amygdala) and brainstem. Processing of non-panic related emotional stimuli is disturbed in PD patients despite clinical remission.